Chronic Rib Osteomyelitis in a Young Adult Female: Diagnostic Challenges and Implications of a Rare Case in a Resource-Limited Setting - Bikash Pandey; Pujan Pant; Aayush Bist; Nishant Pandey (Clinical Medicine Insights: Case Reports)
This case report presents a rare instance of chronic rib osteomyelitis in a 23-year-old female from Darchula, an underserved rural area in Nepal. Rib osteomyelitis is uncommon and often diagnosed late due to its subtle presentation. The patient initially presented at a primary care center with a 2-week history of a protruding bony mass in the right upper back, accompanied by foul-smelling discharge and low-grade fever. She was referred to a tertiary hospital, where a CT scan, surgical excision, and biopsy confirmed chronic rib osteomyelitis. This case highlights the diagnostic challenges of rare conditions in rural settings and emphasizes the essential role of community-based healthcare in early identification and referral. It underscores the need for accessible diagnostic facilities, community health education, and a multidisciplinary approach to support patients in resource-limited environments.